MC1R and KIT Haplotypes Associate With Pigmentation Phenotypes of North American Yak (Bos grunniens). (12th November 2019) - Petersen, Jessica L; Kalbfleisch, Theodore S; Parris, Morgan; Tietze, Shauna M; Cruickshank, Jenifer
Abstract: Small numbers of domestic yak ( Bos grunniens ) were imported to North America in the late 19th century indirectly from the Qinghai-Tibetan Plateau. Coat color of yak is of interest for fiber production, aesthetics, and as a potential indicator of recent hybridization with cattle. North American yak are classified into 3 major coat color patterns depending upon the presence and extent of white markings. They are further classified by nose pigmentation (black or gray). The aim of this study was to identify loci involved in white patterning and nose pigmentation of North American yak. Genotyping by mass spectrometry of markers identified through Sanger and whole-genome sequencing revealed a 388 kb haplotype of KIT associated in a semi-dominant manner with white coloration in this population of yak. This KIT haplotype is similar to both a haplotype found in white-faced Chinese yak and to haplotypes found in cattle but is divergent from other Bos species such as bison, gaur, and banteng. Melanocortin 1 receptor ( MC1R ) was implicated as a dominant determinant of black nose color with a single haplotype containing 2 missense mutations perfectly associated with the phenotype. The MC1R haplotype associated with black nose pigment is also similar to cattle haplotypes. No cattle studied, however, shared either of the 2 haplotypes associated with color in yak, suggesting these alleles were introgressed into yak before they were imported to North America. These results provide molecular insight into the history of North American yak and information from which breeders can determine possible color outcomes of matings.